Transition practices as an arena for the development of relational expertise. Issue 2 (15th March 2019) - Rantavuori, Laura; Karila, Kirsti; Kupila, Päivi
ABSTRACT: This article explores relational expertise in boundary crossing in the context of the transition from preschool to primary school. The need to increase collaboration across institutional and professional boundaries in this transition phase is acknowledged in the literature. This study focuses on the obstacles and resources for professional development found in inter-professional meetings. The theoretical framework is based on the ideas of boundary work and relational expertise. In this study, boundary work is seen as a context in which cultural manuscripts become apparent. The authors identify the two main obstacles that cultural manuscripts create for relational expertise: (1) the institutions are not equally positioned as environments of learning and (2) the knowledge of professionals is not shared. Without a shared space for interaction and support for the professional community, not all of the professionals' knowledge is made visible and not all available resources are utilized.